2015
DOI: 10.3347/kjp.2015.53.3.259
|View full text |Cite
|
Sign up to set email alerts
|

<i>Toxoplasma gondii</i> B1 Gene Detection in Feces of Stray Cats around Seoul, Korea and Genotype Analysis of Two Laboratory-Passaged Isolates

Abstract: The increasing prevalence of Toxoplasma gondii infection in the human population in the Republic of Korea (= Korea) is due to various reasons such as an increase in meat consumption. However, the importance of cats in transmitting T. gondii infection through oocysts to humans has seldom been assessed. A total of 300 fecal samples of stray cats captured around Seoul from June to August 2013 were examined for T. gondii B1 gene (indicating the presence of oocysts) using nested-PCR. Fourteen (4.7%) of 300 cats exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 16 publications
3
24
3
Order By: Relevance
“…This is low in comparison with other studies, like the one performed in Portugal, where 20.5% prevalence was found in domestic cats feces samples using the B1 sequence in PCR [14]. However, our study found a higher prevalence compared to that observed in a Korean study, where prevalence was 4.5% [20], and a study in Switzerland, where prevalence was 0.4% [4]. This is the first study in Colombia detecting T. gondii DNA from cats feces samples, but the frequency of positive samples may be lower compared to previous studies with oocyst prevalence reported at 66.6% [30] and seroprevalence at 84.8%-89.3% [10,30].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is low in comparison with other studies, like the one performed in Portugal, where 20.5% prevalence was found in domestic cats feces samples using the B1 sequence in PCR [14]. However, our study found a higher prevalence compared to that observed in a Korean study, where prevalence was 4.5% [20], and a study in Switzerland, where prevalence was 0.4% [4]. This is the first study in Colombia detecting T. gondii DNA from cats feces samples, but the frequency of positive samples may be lower compared to previous studies with oocyst prevalence reported at 66.6% [30] and seroprevalence at 84.8%-89.3% [10,30].…”
Section: Discussioncontrasting
confidence: 99%
“…Wild and domestic felids are the only known definitive hosts with the ability to shed oocysts in their feces. Common pathways of infection include oocyst-contaminated water, soil, and food; tissue cysts in undercooked or raw meat; and congenital transmission [13,20,37,43]. Oocysts are the environmentally resistant form *Corresponding author: oazamorav@uqvirtual.edu.co Parasite 27, 25 (2020) Ó A. Zamora-Vélez et al, published by EDP Sciences, 2020 https://doi.org/10.1051/parasite/2020023 Available online at: www.parasite-journal.org of the parasite and play a key role in transmission to new hosts and ecosystems, generating the need to study humans alongside domestic and wild animal populations [43].…”
Section: Introductionmentioning
confidence: 99%
“…This result may be due to consumption of meat contaminated with Toxoplasma cysts or due to the small number of Toxoplasma oocysts in fecal specimens which are difficult to determine by fecal examination. Similar to our results, a low prevalence of oocysts shedding in cats was determined at 1.2% in Iran [16], at 2.3% in Italy [17], at 0.3% in Japan [18], at 0.14 % in Germany [19], at 0.4% in Switzerland [20], at 4.7% in South Korea [21], at 0.9 in the USA [22], at 0.8% in Thailand [23], at 0.76 % in Finland [24] by microscopy and PCR methods. In contrast to serological studies, examining feces did not show any information about age and gender as risk factors, due to the low prevalence of oocyst shedding by the cats [13,25].…”
Section: Discussionsupporting
confidence: 91%
“…Even in the same country, the rate of positivity varies considerably depending on where the sample was taken, which test method was used, etc [10,[19][20][21]. In Korea, many researchers have investigated the status of feline toxoplasmosis infection [10,[19][20][21][22][23][24]. However, 1 study regarding the status of infection with toxoplasmosis in dogs has been conducted during 2006-2007 [22].…”
Section: Introductionmentioning
confidence: 99%